Fate and pathways of dredged estuarine sediment spoil in response to variable sediment size and baroclinic coastal circulation. (1st February 2015) - Brown, Jennifer M.; Amoudry, Laurent O.; Souza, Alejandro J.; Rees, Jon
Abstract: Most of the world's megacities are located in estuarine regions supporting commercial ports. Such locations are subject to sedimentation and require dredging to maintain activities. Liverpool Bay, northwest UK, is a region of freshwater influence and hypertidal conditions used to demonstrate the impact of baroclinicity when considering sediment disposal. Although tidal currents dominate the time-varying current and onshore sediment movement, baroclinic processes cause a 2-layer residual circulation that influences the longer-term sediment transport. A nested modelling system is applied to accurately simulate the circulation during a three month period. The hydrodynamic model is validated using coastal observations, and a Lagrangian particle tracking model is used to determine the pathways of 2 sediment mixtures representative of locally dredged material: a mix of 70% silt and 30% medium sand and a mix of 50% fine sand and 50% medium sand. Sediments are introduced at 3 active disposal sites within the Mersey Estuary in 2 different quantities (500 and 1500 Tonnes). Following release the majority (83% or more) of the particles remain within the estuary due to baroclinic influence. However, particles able to leave follow 2 distinct pathways, which primarily depend on the sediment grain size. Typically the finer sediment moves north and the coarser sediment west. Under solely barotropic conditions larger sediment volumes (up to 5 times more) can leave the estuary in a diffuse plume moving north. This demonstrates the necessity of considering baroclinic influence even within a hypertidal region with low freshwater inflow for accurate particle tracking studies. Highlights: POLCOMS is shown to be an accurate estuarine modelling system. The need for accurate sediment sizes to simulate multiple transport pathways is shown. Sediment volume and size fractions are shown to be influential on erosion rate. Baroclinicity is found to control long-term transport in hypertidal regimes.